1978
DOI: 10.1126/science.625660
|View full text |Cite
|
Sign up to set email alerts
|

DNA Synthesis in Cartilage Cells Is Stimulated by Oscillating Electric Fields

Abstract: External oscillating electric fields (1166 volts per centimeter, 5 hertz) enhanced the incorporation of [3H] thymidine into the DNA of chondrocytes isolated from the proliferative layer of embryonic (16 days) chick epiphysis. Verapamil or tetrodotoxin at 10(-6)M concentrations completely blocked the electric field effect. Tetracaine reduced the incorporation of [3H] thymidine in both control and electrically stimulated cells. The findings support the hypothesis that Na and Ca2 fluxes generated by the electrica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
60
0
1

Year Published

1981
1981
2012
2012

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 223 publications
(67 citation statements)
references
References 39 publications
6
60
0
1
Order By: Relevance
“…Satake et al 23 found that calcium concentration in human periodontal ligament fibroblast cells was increased in the presence of PEMF. At the cellular level, Rodan et al 24 observed that cyclic nucleotides and calcium vehicles carry extracellular messages across the cell membrane. Interactions with diffusible ions, such as Ca2 + and K + , may convey an electric signal for DNA synthesis and cell division.…”
Section: Discussionmentioning
confidence: 99%
“…Satake et al 23 found that calcium concentration in human periodontal ligament fibroblast cells was increased in the presence of PEMF. At the cellular level, Rodan et al 24 observed that cyclic nucleotides and calcium vehicles carry extracellular messages across the cell membrane. Interactions with diffusible ions, such as Ca2 + and K + , may convey an electric signal for DNA synthesis and cell division.…”
Section: Discussionmentioning
confidence: 99%
“…Rodan (1978) noted an enhancement of DNA synthesis in stimulated chick epiphyseal chondrocytes, but not in other non skeletal tissues. Norton ( 1979) stimulating embryonic rat calvaria cells and adding 3H-thymidine, also observed an increase in DNA synthesis in the area facing the cathode.…”
Section: Infroductionmentioning
confidence: 91%
“…What can induce such metaplasia is completely unknown, even if it could be logically suspected that they are a consequence of physical stress, ischemia or other unknown factors [66]. For example, the synthesis of the DNA of the cartilaginous cells is stimulated by oscillating electric fields [77], but it can be supposed that such an effect exists in the fibrous body or near to it [66]. Cartilaginous meta-hyperplasia of the central fibrous body has already been described in cases of cardiac sudden death [1,66,67].…”
Section: Cartilaginous Meta-hyperplasia Of the Central Fibrous Bodymentioning
confidence: 99%